Colour vision status of staff working with radiation in public hospital - Bariah Mohd-Ali,; Wong, Mei Yee; Bashirah Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Growing application of radiation sources and lack of awareness among workers in practicing protective measures imply an increased risk of radiation exposure to eye. This study determined the status of colour vision and its association with working duration amongst staff working with radiation in a university hospital. A total of 55 employees (28 exposed (RS) and 27 not directly exposed to radiation (NRS)) were recruited and 30 employees were used as controls. Visual acuity (VA) was measured using Snellen chart. Colour vision assessments were conducted using Ishihara plates, D15 panel and FM 100 hues and the results were analysed using one way ANOVA. The subjects’ age ranged between 29 and 44 years old. Mean VA for all subjects was 6/6. More than 50% of the subjects has colour defects, 3.45% of RS failed D15, 37.93% failed FM 100 hue, 7.4% of NRS failed D15 and 55.56% failed FM 100 hue. Significant difference was found in the total error scores between RS (77.10 ± 6.05) and NRS (84.89 ± 7.76) with the controls (41.47 ± 3.10) [ANOVA F(2,83)=16.084, p=0.00]. There was no association between working duration and severity of colour defect [r(104)= -0.123, p>0.05]. This study concludes that majority of the studied subjects has color deficiency but not significantly correlated with their working duration. Protective measures need to be taken to improve the situation.